2022
DOI: 10.3390/cancers14184533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selected Non-Coding RNAs and Gene Expression Profiles between Common Osteosarcoma Cell Lines

Abstract: Osteosarcoma (OS) is a bone tumour affecting adolescents and elderly people. Unfortunately, basic treatment methods are still underdeveloped, which has a high impact on the poor survivability of the patients. Studies designed to understand the underlying mechanisms of osteosarcoma development, as well as preclinical investigations aimed at establishing novel therapeutic strategies, rely significantly upon in vitro models, which apply well-established cell lines such as U-2 OS, Saos-2 and MG-63. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Several studies have shown miR-223 to have regulatory potential (Taïbi et al, 2014;Jung et al, 2022;Sikora et al, 2022;Tanigawa et al, 2022). Furthermore, miR-223-3p was found to be highly expressed in active-phase E. granulosus tissue (Mariconti et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown miR-223 to have regulatory potential (Taïbi et al, 2014;Jung et al, 2022;Sikora et al, 2022;Tanigawa et al, 2022). Furthermore, miR-223-3p was found to be highly expressed in active-phase E. granulosus tissue (Mariconti et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Extensive research has implicated MMPs in cancer progression [2]. MMP-2, MMP-7, MMP-9, and MMP-14 have been linked to the progression and metastasis of osteosarcoma [40,41]. Xu et al reported that berberine inhibits the migration and invasion of osteosarcoma cells by downregulating the expression of MMP-2 and MMP-9s [42].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that miRNAs are abnormally regulated in human malignancies, including OS, and act as a novel class of oncogenes or tumor suppressors. Literature data on the role of miRNAs in various OS cell lines suggest an important role of miRNAs in the progression of OS [26,27]. Other studies suggest that miRNAs play a central role in the pathogenesis of OS [24].…”
Section: Molecular Basis Of Os Pathogenesis 21 the Role Of Mirnas In ...mentioning
confidence: 99%
“…In addition to the cell subpopulations described, MSCs from bone marrow and adipose tissue (hASCs) [27,343], which are involved in cell proliferation, progression, and metastasis, are an important component of the OS tumor microenvironment [344].…”
Section: Heterogeneity Of the Cellular Component Of The Os Substratementioning
confidence: 99%